Development and characterization of a rat brain metastatic tumor model by multiparametric magnetic resonance imaging and histomorphology - Wang, Shuncong; Chen, Lei; Feng, Yuanbo; Yin, Ting; Yu, Jie; De Keyzer, Frederik; Peeters, Ronald; Van Ongeval, Chantal; Bormans, Guy; Swinnen, Johan; Soete, Jeroen; Wevers, Martine; et al. (Clinical & experimental metastasis, 2022)
To facilitate the development of new brain metastasis (BM) treatment, an easy-to-use and clinically relevant animal model with imaging platform is needed. Rhabdomyosarcoma BM was induced in WAG/Rij rats. Post-implantation surveillance and characterizations were systematically performed with multiparametric MRI including 3D T1 and T2 weighted imaging, diffusion-weighted imaging (DWI), T1 and T2 mapping, and perfusion-weighted imaging (PWI), which were validated by postmortem digital radiography (DR), µCT angiography and histopathology. The translational potential was exemplified by the application of a vascular disrupting agent (VDA). BM was successfully induced in most rats of both genders (18/20). Multiparametric MRI revealed significantly higher T2 value, pre-contrast-enhanced (preCE) T1 value, DWI-derived apparent diffusion coefficient (ADC) and CE ratio, but a lower post-contrast-enhanced (postCE) T1 value in BM lesions than in adjacent brain ( p < 0.01). PWI showed the dynamic and higher contrast agent uptake in the BM compared with the adjacent brain. DR, µCT and histopathology characterized the BM as hypervascular tumors. After VDA treatment, the BM showed drug-related perfusion changes and partial necrosis as evidenced by anatomical, functional MRI parameters and postmortem findings. The present BM model and imaging modalities represent a feasible and translational platform for developing BM-targeting therapeutics.